2012
DOI: 10.1051/0004-6361/201118090
|View full text |Cite
|
Sign up to set email alerts
|

A third cluster of red supergiants in the vicinity of the massive cluster RSGC3

Abstract: Context. Recent studies have shown that the area around the massive, obscured cluster RSGC3 may harbour several clusters of red supergiants. Aims. We analyse a clump of photometrically selected red supergiant candidates 20 south of RSGC3 in order to confirm the existence of another of these clusters. Methods. Using medium-resolution infrared spectroscopy around 2.27 μm, we derived spectral types and velocities along the line of sight for the selected candidates, confirming their nature and possible association… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
9
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 33 publications
(12 citation statements)
references
References 40 publications
3
9
0
Order By: Relevance
“…Following Fig. 2 in González-Fernández & Negueruela (2012), the CO EW ≈ 11 Å of CEN 34 suggests an early-K giant or mid-G supergiant, and the latter agrees well with the previously classified spectral type and luminosity class, if the involved uncertainty is considered.…”
Section: Co Bandhead Absorptionsupporting
confidence: 86%
“…Following Fig. 2 in González-Fernández & Negueruela (2012), the CO EW ≈ 11 Å of CEN 34 suggests an early-K giant or mid-G supergiant, and the latter agrees well with the previously classified spectral type and luminosity class, if the involved uncertainty is considered.…”
Section: Co Bandhead Absorptionsupporting
confidence: 86%
“…The EW of CO bandhead increases linearly with temperature declining for giants and supergiants, respectively, and the latter has higher EW than the former of the same effective temperature (e.g., González-Fernández & Negueruela 2012). The CO bandhead of B273A coincides in depth and width with that of the reference star, a G4 giant (see Fig.…”
Section: Sinfoni Near-ir Spectroscopy Of Point Sourcesmentioning
confidence: 76%
“…of CO bandhead for B273A to be ≈3.5 Å, which suggests a spectral type of G4/G5 for a giant and G2/G3 for a supergiant when following Fig. 2 in González-Fernández & Negueruela (2012). Alternatively, we checked the EW of CO bandhead for the main-sequence stars catalogued by Wallace & Hinkle (1997) and found that B273A's CO bandhead strength is between that of a G8 V (HR 4496) and a K2 V (HR 1084) star.…”
Section: Sinfoni Near-ir Spectroscopy Of Point Sourcesmentioning
confidence: 97%
“…Young massive star clusters (>10 4 M ) where we can find a coeval sample of massive stars at uniform metallicity are excellent laboratories to study massive stellar evolution, star formation process and abundance patterns in galaxies. Recently, several RSGCs (RSGC1, RSGC2, RSGC3, RSGC4, RSGC5, and Alicante 10) are found near Scutum-Crux arm in the Milky Way (Figer et al 2006;Davies et al 2007;Clark et al 2009;Negueruela et al 2010Negueruela et al , 2011Gonzalez-Fernandez & Negueruela 2012), and they are showing very interesting chemical abundance patterns regarding to the Galactic metallicity gradients. The high-resolution spectroscopic studies for the limited samples of RSGs in RSGC1, RSGC2, and RSGC3 (Davies et al 2009;Origlia et al 2016) report that the average metal abundances of the clusters are about subsolar, which is conflict with increasing metal abundance trend at lower R GC .…”
Section: Introductionmentioning
confidence: 99%